Current Based Condition Monitoring of Three Phase Induction Motor Using Deep Learning - Deepak Pawade; Hrishikesh Kulkarni; Ganesh Kulkarni; Akash Vanarse; Dr. Sachin Bhoite (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Condition Monitoring and Predictive maintenance of induction motors might prove quite profitable in the long run since these machines constitute the majority of the industries. Many factories spend lots of money on Reactive and Preventive maintenance which can be lessened using predictive maintenance. Usually, it involves estimating when faults will occur (Remaining useful life aka RUL) of the machine. Motor Current Signature Analysis is one of the techniques employed to identify these faults. However, it's limited to a certain extent. In this paper, we try to predict the voltage faults and RPM of the motor using only the current signals.